Germination Methods and Characteristics of Endemic Centaurea olympica DC. Koch Grown in Cultural Conditions - Yucel, Gul; Erken, Kamil (North Carolina State Univ Dept Wood & Paper Sci, 2023)
The most suitable generative production method was selected in this work by applying different treatments to endemic Centaurea olympica seeds. The development performance and adaptation ability of the species in natural and cultural conditions (in the natural population, in pots and in the garden) were determined, with the goal to protect the species under ex situ conservation. The growth performance of the plant was monitored, and its ornamental plant potential was evaluated. The obtained data were compared with the data from the natural population. All morphological and phenological observations showed that the species can easily adapt to cultural conditions. For 2 months in the summer period, it is a lilac-flowered herbaceous plant that can be preferred for gardens with increasing number of shoots and flowers in parallel with its development. Among the different pretreatments applied to the seeds of the species, the highest germination percentage (73.5%) and germination speed (T5o=8 days) was found with 600 ppm GA3 treatment for 24 h after cold-wet stratification at 4 degrees C for 3 months. The appropriate germination temperature was determined as 20 degrees C.
Keywords: Centaurea olympica; Endemic plant; Generative production; Ornamental properties